2021
DOI: 10.3389/fimmu.2021.654587
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Depletion and Elevation of IFN-γ Dependent Chemokines CXCL9 and CXCL10 in Children With Multisystem Inflammatory Syndrome

Abstract: BackgroundSARS-CoV-2 occurs in the majority of children as COVID-19, without symptoms or with a paucisymptomatic respiratory syndrome, but a small proportion of children develop the systemic Multi Inflammatory Syndrome (MIS-C), characterized by persistent fever and systemic hyperinflammation, with some clinical features resembling Kawasaki Disease (KD).ObjectiveWith this study we aimed to shed new light on the pathogenesis of these two SARS-CoV-2-related clinical manifestations.MethodsWe investigated lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 56 publications
11
70
0
Order By: Relevance
“…IL-6 is a major pro-inflammatory cytokine that was reportedly elevated in patients with MIS-C in previous studies (15)(16)(17)(18)(19)(20)22). In our patient, IL-6 titer also rapidly increased (21.1-fold) with the onset of symptoms.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…IL-6 is a major pro-inflammatory cytokine that was reportedly elevated in patients with MIS-C in previous studies (15)(16)(17)(18)(19)(20)22). In our patient, IL-6 titer also rapidly increased (21.1-fold) with the onset of symptoms.…”
Section: Discussionsupporting
confidence: 70%
“…The clinical significance of cytokines with titers that did not immediately decline to baseline after the fifth day of illness (but showed a gradual decline; Figure 3C ) is difficult to determine on the basis of data from our single patient; however, Caldarale et al showed that IL-6, CXCL8, CCL2, CXCL9, and CXCL10 were higher in MIS-C patients than in pediatric COVID-19 patients, and that treatment with IVIG and methylprednisolone resulted in a rapid decrease in IL-6, but the decrease of CCL 2, CXCL9, and CXCL10 were delayed ( 22 ). The same changes in these cytokines/chemokines were observed in our study.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations